The Economic and Environmental Importance of Plant- Pathogenic Nematodes of Date Palm Phoenix dactylifera L. and Their Control Method- Review Article - Abed, Ali Z.; Ofi, Baida G.; Abass, Mohammed H. (Basrah Journal Of Date Palm Research, 2025)
Plant-parasitic nematodes cause significant economic losses in agricultural production, leading to approximately 10-30% losses of the total global agricultural production value annually. In cases of severe infestation and soil contamination by nematodes, this percentage can reach 80% or more. The severity and type of damage caused by nematodes depend on different factors, such as the species of nematode, the variety of host plant, as well as, the environmental conditions. Among the many plants affected by nematodes, the date palm (Phoenix dactylifera L.) stands out as particularly susceptible to several parasitic genera of nematodes, which cause significant economic losses, in addition to transmitting numerous fungal, viral, and other disease agents. Hence, the degree of infection varies among the pathogenic genera of nematodes affecting date palms, and the severity of symptoms depend on many factors, including those related to the parasite itself, the host, and environmental conditions and their interaction. Managing nematodes diseases, mainly requires the use of expensive chemical pesticides, which increases operational costs for farmers and affects the economic viability of agricultural production. Strategies to mitigate these losses include implementing good agricultural practices, including crop rotation and the use of resistant varieties, improving soil and water management, and employing biological control methods using beneficial organisms, such as fungi and bacteria that are antagonistic to nematodes. Solar soil sterilization is also used to reduce nematode severity.